Hydrocarbon seal quantification : papers presented at the Norwegian Petroleum Society Conference, 16-18 October 2000, Stavanger, Norway - Koestler, Andreas, 1953-; Hunsdale, Robert (Elsevier, 2002)
This volume contains 17 selected papers reflecting the flavour of the Norwegian Petroleum Society conference on hydrocarbon seals quantification and showing the recent significant advances in the understanding and application of hydrocarbon seal methodologies. Three broad categories are covered in this book: methodologies addressing cap-rock integrity, methodologies relating to fault seal and case studies both from the hydrocarbon basins of Northwestern Europe and in the form of outcrop examples. With the North Sea, Norwegian Sea and Atlantic Margin moving along their respective basin maturity and development curves, exploration is being forced deeper into high pressure/high temperature terrains, while exploitation and development requires greater precision and realism in reservoir simulations to maximise drilling strategies to prolong field life. In all instances the need for predictive tools and methodologies that address the integrity and behaviour of top and lateral (fault) seals to hydrocarbon traps, both in the static and dynamic state, have been identified as key risk factors and this is reflected in this volume.
Keywords: Traps (Petroleum geology) -- Congresses.; Petroleum -- Geology -- Congresses.; elektronické knihy; electronic books